Phylodynamic analysis of foot-and-mouth disease virus evolution in Mar Chiquita, Argentina - Lozano Calderon, Laura Camila; Cabanne, Gustavo Sebastián; Marcos, Andrea; Galdo Novo, Sabrina; Torres, Carolina; Perez, Andres; Pybus, Oliver G.; Konig, Guido Alberto (Springer, 2024)
Foot-and-mouth disease is a highly contagious disease affecting cloven-hoofed animals, resulting in considerable economic losses. Its causal agent is foot-and-mouth disease virus (FMDV), a picornavirus. Due to its error-prone replication and rapid evolution, the transmission and evolutionary dynamics of FMDV can be studied using genomic epidemiological approaches. To analyze FMDV evolution and identify possible transmission routes in an Argentinean region, field samples that tested positive for FMDV by PCR were obtained from 21 farms located in the Mar Chiquita district. Whole FMDV genome sequences were obtained by PCR amplification in seven fragments and sequencing using the Sanger technique. The genome sequences obtained from these samples were then analyzed using phylogenetic, phylogeographic, and evolutionary approaches. Three local transmission clusters were detected among the sampled viruses. The dataset was analyzed using Bayesian phylodynamic methods with appropriate coalescent and relaxed molecular clock models. The estimated mean viral evolutionary rate was 1.17 × 10− 2 substitutions/site/year. No significant differences in the rate of viral evolution were observed between farms with vaccinated animals and those with unvaccinated animals. The most recent common ancestor of the sampled sequences was dated to approximately one month before the first reported case in the outbreak. Virus transmission started in the south of the district and later dispersed to the west, and finally arrived in the east. Different transmission routes among the studied herds, such as non-replicating vectors and close contact contagion (i.e., aerosols), may be responsible for viral spread.